4.9% Efficient Sb2S3 Solar Cells from Semitransparent Absorbers with Fluorene-Based Thiophene-Terminated Hole Conductors - Mandati, Sreekanth; Juneja, Nimish; Katerski, Atanas; Jegorovė, Aistė; Grzibovskis, Raitis; Vembris, Aivars; Dedova, Tatjana; Spalatu, Nicolae; Magomedov, Artiom; Karazhanov, Smagul; Getautis, Vytautas; Krunks, Malle (American Chemical Society, 2023)
Fluorene-based hole transport materials (HTMs) with terminating thiophene units are explored, for the first time, for antimony sulfide (Sb2S3) solar cells. These HTMs possess largely simplified synthesis processes and high yields compared to the conventional expensive hole conductors making them reasonably economical. The thiophene unit-linked HTMs have been successfully demonstrated in ultrasonic spray-deposited Sb2S3 solar cells resulting in efficiencies in the range of 4.7-4.9% with an average visible transmittance (AVT) of 30-33% (400-800 nm) for the cell stack without metal contact, while the cells fabricated using conventional P3HT have yielded an efficiency of 4.7% with an AVT of 26%. The study puts forward cost-effective and transparent HTMs that avoid a post-coating activation at elevated temperatures like P3HT, devoid of parasitic absorption losses in the visible region and are demonstrated to be well aligned for the band edges of Sb2S3 thereby ascertaining their suitability for Sb2S3 solar cells and are potential candidates for semitransparent applications. © 2023 The Authors. Published by American Chemical Society under the CC BY 4.0 and CC BY-NC-ND 4.0 licence.
The “Development of Semitransparent Bifacial Thin-Film Solar Cells for Innovative Applications” benefits from a 999372 € grant from Iceland, Liechtenstein, and Norway through the EEA Grants. The aim of the project is to develop a new approach based on novel materials and structures and production technologies, which are the key to further increase the share and range of applications of PV in areas with sub-average sunlight, including Baltic and Nordic countries. Therefore, the development of resource saving, cost-effective, and efficient PV devices is a primary challenge of this project. Project contract with the Research Council of Lithuania (LMTLT) number is S-BMT-21-1(LT08-2-LMT-K-01-003). Department of Materials and Environmental Technology, Tallinn University of Technology has received funding from the Estonian Research Council projects PRG627 “Antimony chalcogenide thin films for next-generation semitransparent solar cells applicable in electricity producing windows” and PSG689 “Bismuth Chalcogenide Thin-Film Disruptive Green Solar Technology for Next-Generation Photovoltaics”, and the Estonian Centre of Excellence project TK141 (TAR16016EK) “Advanced materials and high-technology devices for energy recuperation systems”, the European Union’s Horizon2020 program under the ERA Chair project 5GSOLAR grant agreement No 952509. Institute of Solid-State Physics, University of Latvia has received funding from the European Union’s Horizon2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement no. 739508, project CAMART. The authors thank Dr. Tadas Malinauskas and Dr. Valdek Mikli for their support in the preparation and characterization of the samples.
Keywords: Research Subject Categories::NATURAL SCIENCES; antimony sulfide; hole transport material; semitransparent; solar cells; thiophene